Contribution of Rare and Common APOE Variants to Familial Hypercholesterolemia in Spanish Cohort - Lorena M. Vega-Prado; Daniel Vázquez-Coto; Francisco Villazón; Lorena Suárez-Gutiérrez; Ceferino Martínez-Faedo; Edelmiro Menéndez-Torre; María Riestra; Silvia González-Martínez; Gala Gutiérrez-Buey; Claudia García-Lago; Juan Gómez; Victoria Alvarez; et al. (Cardiogenetics)
Our aim was to determine whether rare APOE pathogenic variants (PV) and the common e2/e3/e4 polymorphism were associated with the risk of familial hypercholesterolemia (FH). A total of 431 patients who met the inclusion criteria for FH were next-generation sequenced for the main candidate genes (LDLR, APOB, PCSK9, APOE, LDLRAP1). A total of 139 patients (32%) had a pathogenic variant, including 3 with APOE p.Leu167del. Among the PV-negatives (n = 292), one was homozygous for APOE-e2 and showed a combined phenotype of high low-density lipoprotein cholesterol (LDL-C) and triglycerides (TGs). A total of 165 population controls were also genotyped for the APOE polymorphism. PV-negative patients showed a significantly higher frequency of APOE-e3e4/e4e4 compared to PV-positives (p = 0.006) and to population controls (p = 0.0002, OR = 2.63, 95% CI = 1.57–4.40). APOE-e4e4 patients had significantly higher mean LDL-C compared to the other genotypes (p = 0.047). In conclusion, APOE pathogenic variants were a rare cause of FH in our population, and the APOE-e4 allele was a significant risk factor for being diagnosed with familial hypercholesterolemia in the absence of a pathogenic variant involved in FH. In particular, the APOE-e4e4 genotype was associated with higher LDL-C levels compared to the other genotypes.